Bioconcrete as an alternative sustainable construction material - Abbas Ali; Abdalla Khalid; Chalklen Thomas; de Lussy Kubisa Laurence; Tann David; Ivankovic Davor; Andersson Liv; Kazi Silvia (MATEC Web of Conferences)
The overall aim of the present research project is to examine the feasibility of industrialising a disruptive, carbon negative bio-concrete technology (developed by Biozeroc). The innovative technology uses bacteria to synthesise limestone which is used to bind aggregates. This eliminates the need for the high- temperature lime calcination process associated with ordinary Portland cement, the current preferred method for aggregate binding, which is responsible for 7~8 % of global green house gas emissions. This results in a concrete solution that can contribute to addressing the urgent need to address the climate emergency and help the construction industry achieve its NetZero targets. The main objective of the present study is to experimentally examine the material and structural performance of the newly-developed Microbially Induced Calcite Precipitation (MICP) bio-concrete and compare it to traditional ordinary Portland cement (OPC) concrete. This will be mainly based on examining the fresh and hardened properties of MICP and OPC concrete. The aim is to establish data-based guidelines for the uptake of an innovative and sustainable MICP concrete product within the construction industry. The outcome of these studies will be useful to manufacturers, practicing engineers, particularly designers and specifiers and to the concrete sector as a whole.